PERILAKU BELAJAR PESERTA DIDIK DITINJAU DARI POLA ASUH OTORITER ORANGTUA - Afiif, Ahmad; Kaharuddin, Fajriani (AULADUNA: Jurnal Pendidikan Dasar Islam, 2015)
Abstract: This research  aimed investigating the authoritative parenting style of parents on students' learning behavior. The problem statement of this research were: (1) what was the description of parents' authoritative style?; (2) what was the description of students' learning behaviour?; (3) did the authoritative style of parents significantly influenced the students' learning behaviour? The design of the research was a quasi experiment and took the subjects from the fifth and the sixth grade students of the the 50 State elementary school Bonto Panua Pangkep. The results showed that there was a significant influence of parents' authoritative style on the students' learning behaviour. The implication of this research was the important of the adults' self control aspect towards children's learning development.Abstrak: Penelitian ini bertujuan mengetahui pengaruh pola asuh otoriter orangtua terhadap perilaku belajar peserta didik. Rumusan masalah dalam penelitian ini adalah: (1) Bagaimana gambaran pola asuh otoriter orangtua peserta didik; (2) Bagaimana gambaran perilaku belajar peserta didik; dan (3) Apakah pola asuh otoriter orangtua berpengaruh secara signifikan terhadap perilaku belajar peserta didik. Penelitian ini adalah penelitian quasi experimental terhadap peserta didik kelas V dan VI di SD Negeri 50 Bonto Panno Kabupaten Pangkep. Hasilnya menunjukkan bahwa terdapat pengaruh pola asuh otoriter orangtua terhadap perilaku belajar peserta didik. Penelitian ini berimplikasi kepada pentingnya aspek pengendalian diri orang dewasa terhadap perkembangan belajar anak.